Effects of soybean isoflavones on reproductive organ development and biochemical indices of male Xiang pigs - FAN Jue-xin; ZHANG Bin; LI Li-li; YUAN Xiao-xue; GENG Mei-mei; LUO Jia-jie (浙江大学学报. 农业与生命科学版, 2012)
To investigate the effects of soybean isoflavones (SI) on growth performance, reproductive organ development, testis and epididymis biochemical indices of male Xiang pigs, 50 healthy male pigs aged 28 d were selected and divided at random into five groups (10 pigs per group). The pigs in group 1, 2, 3 and 4 were fed basal diet with 0, 125, 250, 500 mg·kg-1 SI respectively, while the pigs in group 5 fed basal diet with 0.5 mg·kg-1 diethylstilbestrol for 60 d. Five pigs of each group were slaughtered at the end of the feeding period to determine the mass of reproductive organs, and to analyze several biochemical indices in testis and epididymis of the pigs. The results showed that there were no significant differences (P>0.05) in growth performance among the different treatments. However, the relative testis mass of the pigs in group 3 was greater (P<0.05) than that in group 1 and the relative prostate mass and seminal vesicle one of the pigs in group 3 were less (P<0.05) than those in group 1. By contrast, the relative testis mass and epididymis one were less (P<0.05) than those in group 1. Moreover, the testis' α-glucosidase concentration of all treatments, the lactate dehydrogenase (LDH) concentration in testis and the carnitine and α-glucosidase in epididymis of the pigs in group 4 were significantly higher (P<0.01) than those in group 1. But the gamma-glutamyl transpeptidase (GGT) concentrations in epididymis of the pigs in group 2 and 3 were less (P<0.05), and the malondialdehyde (MDA) concentration in testis of the pigs in group 3 was higher (P<0.05) than those in group 1. Compared with the positive control, 500 mg·kg-1 SI in diet could improve the GGT concentration (P<0.01) and the LDH concentration (P<0.05) of the testis; but 250 mg·kg-1 SI had adverse effect on the GGT concentration of the epididymis (P<0.01), and 125 mg·kg-1 SI could decrease the carnitine, α-glucosidase, GGT concentration (P<0.01) and fructose concentration (P<0.05). The MDA concentration was higher in testis (P<0.05) of the pigs in group 3 than that in group 5. In conclusion, different levels of SI supplemented in the diet of male Xiang pigs can cause different effects on reproductive organs. The level of SI that cause adverse effect on male reproductive organs may be in the range of 250-500 mg·kg-1.